Vasoactive genes as molecular and genetic predictors of severe preeclampsia - Tatiana E Belokrinitskaya; Nataliya I Frolova; Natal'ia N Strambovskaya; Kristina A Kolmakova (IP Berlin A.V., 2019)
Aim. To analyze an incidence rate of polymorphisms and combinations of genes AGT-704T> C, AGT-521C> T, AGTR1-1166A> C, AGTR2-1675G> A, еNO3-786T> C, еNOS3-894G> C, ADD1-1378G> T, CYP11B2 -304C> T, GNB3-825C> T and to assess their association with a risk of severe pre-eclampsia. Materials and methods. The study included women of early fertile age (20-35 years old) with spontaneous singleton pregnancy, no bad habits (smoking, alcohol or drug use), no extragenital diseases and no family (mother or sister) or an individual history of pre-eclampsia and with body mass index in the first trimester of pregnancy less than 35 kg/m2. The study group consisted of 100 patients with severe preeclampsia and the control group included 100 women with uncomplicated pregnancy. Genotyping was carried out by method of polymerase chain reaction. Data analysis included compliance with the Hardy - Weinberg law, Cramer's V criterion, χ2 test, odds ratio (OR) and its 95% confidence interval (CI). To assess a distribution of stated polymorphisms of genes and their alleles a general (χ2 test, df=2) and multiplicative (χ2 test, df=1) inheritance models were used. Results and discussion. Patients with severe pre-eclampsia had statistically significantly higher incidence rate of mutant homozygous genotypes AGTR1-1166CC (χ2=5,54; p=0,05) and еNO3-786CC (χ2=23,05; p=1,0E-5). A significant association between a carrier of the mutant homozygous genotype eNO3-786СC (χ2=19,780; p=0,000) and severe pre-eclampsia (OR 45,07, 95% CI 2,68-759,30) was found out. Combinations of mutant alleles of potentially predictive polymorphisms of vasoactive genes in women with preeclampsia were recorded 7,7 times more often (23% vs 3%; χ2=17,683, p=0,000; average Cramer's V link) which led to a significant association link with a risk of a disease complication (OR 9,658, 95% CI 2,795-33,367). Conclusion. A synergistic interaction between polymorphic loci in severe preeclampsia was established. The mutant homozygous genotype eNO3-786СC as well as a combination of at least two mutant alleles of genes - candidates for arterial hypertension or their combination with the mutant gene ADD1-1378TT or GNB3-825TT can claim a role of molecular and genetic predictors of severe preeclampsia.